The current state of xenotransplantation - Zeyland, J. (J Appl Genet, 2014)
Pigs as a source of grafts for xenotransplantation can help to overcome the rapidly growing shortage of human donors. However, in the case of pig-to-human transplantation, the antibody-xenoantigen complexes lead to the complement activation and immediate hyperacute rejection. Methods eliminating hyperacute rejection (HAR) include α1,3-galactosyltransferase (GGTA1) inactivation, regulation of the complement system and modification of the oligosaccharide structure of surface proteins. The humoral immune response control and reduction of the risk of coagulation disorders are the priority tasks in attempts to overcome acute humoral xenograft rejection that may occur after the elimination of HAR. The primary targets for research are connected with the identification of obstacles and development of strategies to tackle them. Because of the magnitude of factors involved in the immune, genetic engineers face a serious problem of producing multitransgenic animals in the shortest possible time.